(untitled) (Journal of Innovation in Academia, 2025)
This paper analyzes how Adichie’s Americanah redefines the notion of immigrant’s identity and explores transnational ethos in relation to the concepts of nationality, globalization, home, and culture through the portrayal of two Nigerian lovers Ifemelu and Obinze. To carry out the analysis, we use theoretical insights from Transnational Studies which revolves around the life of people living in a globalized world. Adichie portrays her Nigerian characters like Ifemelu in transnational context not only to critique Western multicultural ethos—policy to encourage transnational immigrants to assimilate to mainstream culture of the hostland—but also to valorize the role of transnational subjects like Ifemelu for the development of their homeland even in the age of ‘globalization’.